2020
DOI: 10.1021/acsanm.0c01058
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom-Derived Carbon Dots for Toxic Metal Ion Detection and as Antibacterial and Anticancer Agents

Abstract: Although carbon nanoparticles or quantum dots (C-dots) have been studied extensively for a variety of applications (e.g., photocatalysis, metal ion sensing, antibacterial, cell labeling), a greener synthetic method is highly indispensable. Herein, we report a facile one-step hydrothermal carbonization approach for the synthesis of fluorescent blue/green C-dots using oyster mushroom (Pleurotus species). First, we demonstrate the application of these C-dots as a colorimetric sensor for toxic metal ions detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(106 citation statements)
references
References 74 publications
5
101
0
Order By: Relevance
“…The nano size facilitated distribution in the cytoplasm and non-toxic nature revealed their biocompatibility which widen their scope in imaging and antibacterial drug delivery [ 89 ].The NCDs prepared by oyster mushroom ( Pleurotus species) have also demonstrated promising antibacterial activity against Klebsiella pneumonia , Staphylococcus aureus and Pseudomonas aeruginosa as observed by MIC assay (MIC value – 30 μg/mL). The NCDs inhibited the growth of bacteria in a dose dependent manner [ 90 ].The antibacterial activity of NCDs prepared from sea weeds derived from κ- carrageenan and lemon juice by hydrothermal synthesis and then quaternised by benzalkonium chloride (improve the fluorescence property) were promising. These NCDs efficiently inhibited the E. coli bacteria (gram negative) [ 91 ].…”
Section: Applications Of Ncds In Drug Deliverymentioning
confidence: 99%
“…The nano size facilitated distribution in the cytoplasm and non-toxic nature revealed their biocompatibility which widen their scope in imaging and antibacterial drug delivery [ 89 ].The NCDs prepared by oyster mushroom ( Pleurotus species) have also demonstrated promising antibacterial activity against Klebsiella pneumonia , Staphylococcus aureus and Pseudomonas aeruginosa as observed by MIC assay (MIC value – 30 μg/mL). The NCDs inhibited the growth of bacteria in a dose dependent manner [ 90 ].The antibacterial activity of NCDs prepared from sea weeds derived from κ- carrageenan and lemon juice by hydrothermal synthesis and then quaternised by benzalkonium chloride (improve the fluorescence property) were promising. These NCDs efficiently inhibited the E. coli bacteria (gram negative) [ 91 ].…”
Section: Applications Of Ncds In Drug Deliverymentioning
confidence: 99%
“…[31] The characteristic peaks at 1671 cm À 1 ,1574 cm À 1 and 1448 cm À 1 were assigned to C=O, C=C and CÀ N stretching vibration, [32] respectively. The strong peaks at 1384 cm À 1 were assigned to the stretching vibrations of NÀ H. [33] The peaks at 1279 cm À 1 was assigned to the CÀ N stretching vibrations [34] and the peaks at 2927 cm À 1 and 2977 cm À 1 were due to the CÀ H stretching vibrations. [35] The FTIR results demonstrated that abundant functional groups such as À NH 2 and À COOH existed on the surface of CDs.…”
Section: Characterization Of Cdsmentioning
confidence: 99%
“…16 Furthermore, uorescent CDs also have chemical stability, good aqueous solubility, low cytotoxicity, and high biocompatibility. Owing to these fascinating properties, CDs have been widely applied in uorescence imaging, 17,18 uorescence detection, 19 drug delivery 20 and catalysis. 21 Recently, uorescent CDs have been used to stabilize and reduce metal nanomaterials due to the abundant oxygen containing functional groups (hydroxyl, carbonyl, carboxyl and epoxy) on their surface, which were considered as an excellent electron acceptor and electron donor.…”
Section: Introductionmentioning
confidence: 99%